2015
DOI: 10.1097/sap.0000000000000455
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Computer-Assisted Orthognathic Surgery

Abstract: This computer-assisted orthognathic surgery system helps to improve surgical planning, reduce surgical difficulty, facilitate positioning and fixation of the maxillomandibular complex, and improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 23 publications
2
35
0
1
Order By: Relevance
“…Lin et al . proposed a protocol for assessing the surgical simulation, guide positioning, intraoperative navigation, and outcome validation provided by computer-assisted surgery systems3839. The 3D virtual surgery combined with navigation was proposed and suggested that simulation-guided navigation makes accurate postoperative outcomes possible for maxillary repositioning in orthognathic surgery404142434445.…”
mentioning
confidence: 99%
“…Lin et al . proposed a protocol for assessing the surgical simulation, guide positioning, intraoperative navigation, and outcome validation provided by computer-assisted surgery systems3839. The 3D virtual surgery combined with navigation was proposed and suggested that simulation-guided navigation makes accurate postoperative outcomes possible for maxillary repositioning in orthognathic surgery404142434445.…”
mentioning
confidence: 99%
“…However, a better treatment outcome is obtained, especially for patients with complicated deformity and asymmetry. In our experience, postoperative facial symmetry and harmony have much been improved (Lin et al, 2015). The cost and time are expected to be reduced in the future because of improvements in technology and experience.…”
Section: Discussionmentioning
confidence: 90%
“…Son varios los autores que han presentado sistemas alternativos a las FO clásicas para realizar la transferencia intraoperatoria del plan quirúrgico virtual [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Estos protocolos suelen aplicarse para posicionar el maxilar superior o para facilitar la relación céntrica condilar, y se podrían clasificar en 2 grupos según el sistema de osteosíntesis utilizado: a) grupo 1: reposicionamiento exclusivo: uso de diferentes férulas aplicadas en distinto tiempo o asistido por navegación 8-16 para posicionar el fragmento maxilar; posteriormente la osteosín-tesis se realiza con miniplacas convencionales, y b) grupo 2: reposicionamiento y osteosíntesis simultánea mediante el uso de miniplacas de titanio personalizadas con la ayuda de guías de brocado/osteotomía o sistemas de navegación [17][18][19][20][21][22][23] .…”
Section: Discussionunclassified